Curating Social Image: Experimental Evidence on the Value of Actions and Selfies - Håkan J. Holm; Margaret Samahita (Lund University, School of Economics and Management, Department of Economics, 2016)
We manipulate the information subjects can share on the web concerning socially sensitive actions (public good contribution) and visibility (selfie) to determine the effect on social image, as captured by the price subjects demand for publication. The overall conclusion from the experiment is that theory about social reputation can predict subjects' social-signaling behavior. People take costly decisions to "filter" information about themselves (in retrospect) before it is published. We also report results of a more exploratory nature and find that taking a selfie has a strong negative impact on cooperation among frequent selfie takers, but not on other subjects.
Keywords: C90; C91; D80; D82; 330; social image; selfie; cooperation; signaling